#### Answer

$x=0;x=3$

#### Work Step by Step

$\log _{2}\left( x-2\right) +\log _{2}\left( x-1\right) =1\Rightarrow \log _{2}\left[ \left( x-1\right) \left( x-2\right) \right] =1$
$\Rightarrow x^{2}-3x+2=2^{1}\Rightarrow x^{2}=3x\Rightarrow x=0;x=3$

Published by
Pearson

ISBN 10:
013421742X

ISBN 13:
978-0-13421-742-0

$x=0;x=3$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.